KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP DALAM MENYELESAIKAN SOAL SEGI EMPAT [THE MATHEMATICAL CREATIVE THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING QUADRILATERAL PROBLEMS] - Maharani, Laily Putri; Subanji; Imam Rofiki (Universitas Pelita Harapan, 2025)
This study was conducted with the aim of describing the mathematical creative thinking abilities of ninth-grade students at SMP Negeri 2 and SMP Negeri 19 Malang in solving quadrilateral problems. The research method used was a qualitative descriptive approach. The subjects of the study were ninth-grade students, totaling 337, with 5 selected students as the sample. The data sources in the study were the students themselves, in the form of essay test results, questionnaire sheets, and interview results. The instruments used included essay tests, questionnaires, and interview guidelines. The research data were described in narrative form. The type of triangulation used was methodological triangulation by integrating essay test results, questionnaires, and reinforcing them with interview findings. Based on the results obtained, the students were categorized into levels of creative thinking ability: imitation, modification, and construction. Of the 5 selected subjects, 1 student was at the imitation level, 1 student at the modification level, and 3 students at the construction level. BAHASA INDONESIA ABSTRACT: Penelitian ini dilakukan dengan tujuan untuk memaparkan kemampuan berpikir kreatif matematis siswa kelas IX di SMP Negeri 2 dan SMP Negeri 19 Kota Malang dalam menyelesaikan soal segi empat. Metode penelitian yang digunakan yakni pendekatan kualitatif jenis deskriptif. Subjek penelitian yaitu siswa kelas IX yang berjumlah 337 dengan subjek terpilih sebanyak 5 siswa. Sumber data pada penelitian berupa hasil tes uraian, lembar angket, dan hasil wawancara yang telah dilakukan. Instrumen yang digunakan yaitu tes uraian, angket, dan pedoman wawancara. Data hasil penelitian dideskripsikan dalam bentuk uraian deskripsi. Jenis triangulasi yang digunakan yakni triangulasi metode dengan mengintegrasikan hasil tes uraian, angket, dan diperkuat melalui hasil wawancara. Berdasarkan hasil yang diperoleh, siswa dikategorikan berdasarkan level kemampuan berpikir kreatif yakni level imitasi, modifikasi dan konstruksi. Dari 5 subjek terpilih terdapat 1 siswa termasuk level imitasi, 1 siswa level modifikasi, dan 3 siswa level konstruksi.